The Histamine Pathway is a Target to Treat Hepatic Experimental Erythropoietic ProtoporphyriaSummary - Ning Kuo; Pei Li; Juliana Bragazzi Cunha; Lu Chen; Jordan A. Shavit; M. Bishr Omary (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: Erythropoietic protoporphyria (EPP) is caused by mutations in ferrochelatase, which inserts iron into protoporphyrin-IX (PP-IX) to generate heme. EPP is characterized by PP-IX accumulation, skin photosensitivity, cholestasis, and end-stage liver disease. Despite available drugs that address photosensitivity, treatment of EPP-related liver disease remains an unmet need. Methods: We administered delta-aminolevulinic acid (ALA) and deferoxamine (DFO), which results in PP-IX overproduction and accumulation. High-throughput compound screening of ALA + DFO-treated zebrafish identified chlorcyclizine (first generation H1-antihistamine receptor blocker) as a drug that reduces zebrafish liver PP-IX levels. The effect of chlorcyclizine was validated in porphyrin-loaded primary mouse hepatocytes (PMHs), transgenic Fechm1Pas EPP mice, and mice fed the porphyrinogenic compound 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC). Plasma and tissue PP-IX were measured by fluorescence; livers were analyzed by histology, immunoblotting, and quantitative polymerase chain reaction. Results: Chlorcyclizine-treated zebrafish larvae, DDC-fed, and transgenic EPP mice manifested reduced hepatic PP-IX levels compared with controls. Histamine increased PP-IX accumulation in porphyrin-stressed hepatocytes, whereas H1/H2-receptor blockade decreased PP-IX levels. In both mouse models, chlorcyclizine lowered PP-IX levels in female but not male mice in liver, erythrocytes, and bone marrow; improved liver injury; decreased porphyrin-triggered protein aggregation and oxidation; and increased clearance of stool PP-IX. In PMHs, chlorcyclizine induced nuclear translocation of constitutive androstane and farnesoid X receptors, and transactivated bile acid transporter expression. Knockdown of the transporters BSEP and MRP4 led to increased detection of sequestosome-1 (p62 protein) high-molecular-weight species. Chlorcyclizine also reduced hepatic mast cell number and histamine level in EPP mice. Conclusions: Histamine plays an important role in PP-IX accumulation in zebrafish and 2 experimental EPP models. Chlorcyclizine and/or other antihistamines provide a potential therapeutic strategy to treat EPP-associated liver disease via decreasing PP-IX accumulation.